2022
DOI: 10.3847/2041-8213/ac9b3d
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Mass Loss in Low-mass Type Ib/c Supernova Progenitors

Abstract: Many core-collapse supernovae (SNe) with hydrogen-poor and low-mass ejecta, such as ultra-stripped SNe and type Ibn SNe, are observed to interact with dense circumstellar material (CSM). These events likely arise from the core collapse of helium stars that have been heavily stripped by a binary companion and have ejected significant mass during the last weeks to years of their lives. In helium star models run to days before core collapse we identify a range of helium core masses ≈2.5–3 M ⊙ wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
3
10
1
Order By: Relevance
“…The progenitors of stripped-envelope SNe could either be stripped by binary partners, or they could be very massive stars with strong winds, and progenitor detections in several bands might allow us to distinguish between these two scenarios. Wu & Fuller (2022) predict that late nuclear burning stages trigger mass loss and brightening for stripped stars. Such events would boost the detection rate for these progenitors and offer direct information about the processes in their stellar cores.…”
Section: Discussionmentioning
confidence: 99%
“…The progenitors of stripped-envelope SNe could either be stripped by binary partners, or they could be very massive stars with strong winds, and progenitor detections in several bands might allow us to distinguish between these two scenarios. Wu & Fuller (2022) predict that late nuclear burning stages trigger mass loss and brightening for stripped stars. Such events would boost the detection rate for these progenitors and offer direct information about the processes in their stellar cores.…”
Section: Discussionmentioning
confidence: 99%
“…Tauris et al (2015) found that the maximum mass-loss rate of ultra-stripped helium stars in binary systems is close to ∼10 −4 M e yr −1 . More recently, Wu & Fuller (2022) found that mass loss with rates of    --M M 10 yr 4 1 could last for ∼10 4 yr until core collapses of close-binary low-mass helium stars, while extreme mass loss…”
Section: Methodsmentioning
confidence: 99%
“…For a comprehensive introduction on the stellar massloss, please see the review by Smith (2014). Tauris et al (2015) found that the maximum mass-loss rate of ultra-stripped helium stars in binary systems is close to ∼ 10 −4 M yr −1 .More recently, Wu & Fuller (2022) found that mass loss with rates of Ṁ 10 −4 M yr −1 could last for ∼ 10 4 yrs until core collapses of closebinary low-mass helium stars, while extreme mass loss ( Ṁ 10 −2 M yr −1 ) could possibly occur beginning weeks to decades before SN explosions. The CSM interaction of such winds from ultra-stripped stars in binary systems is supposed to be very complicated.…”
Section: Methodsmentioning
confidence: 99%